Synthesis and antimicrobial activity of 1,4- diaryl-5-miino-3-imidazolin-2-ones - Sharma, Bimal Prasad (Journal of Nepal Chemical Society, 2006)
Fifteen new 1,4-diaryl-5-imino-3-imidazolin-2-ones have been prepared from α-oxonitriles and monochlorophenylureas. The present syntheses offer a simple and convenient method of preparation of the 5-imino-3-imodazotin-2-ones from readily available starting materials. The result of their antimicrobial screening indicate some of them possess significant activity. DOI: 10.3126/jncs.v21i0.216 Journal of Nepal Chemical Society Vol.21 2006 pp.16-18